Comparing the Genetic Diversity and Antimicrobial Resistance Profiles of Campylobacter jejuni Recovered from Cattle and Humans - Cha, Wonhee; Mosci, Rebekah E.; Wengert, Samantha L.; Venegas Vargas, Cristina; Rust, Steven R.; Bartlett, Paul C.; Grooms, Daniel L.; Manning, Shannon D. (Frontiers in Microbiology, 2017)
Campylobacter jejuni, a leading cause of gastroenteritis in humans, is a foodborne pathogen that can reside in chickens, pigs, and cattle. Because resistance to fluoroquinolones and macrolides, which are commonly used to treat human infections, has emerged in C. jejuni, it is imperative to continously monitor resistance patterns and examine the genetic variation in strains from human infections and animal reservoirs. Our previous study of C. jejuni from human campylobacteriosis cases showed a significantly higher rate of tetracycline resistance compared to national trends, and identified multilocus sequence type (ST)-982 and a history of cattle contact to be associated with tetracycline resistance. To further investigate these associations, we conducted a cross-sectional study to determine the frequency of antimicrobial resistance and examine the genetic diversity of C. jejuni recovered from 214 cattle at three Michigan herds. Overall, the prevalence of C. jejuni was 69.2% (range: 58.6–83.8%) for the three farms, and 83.7% (n = 113) of isolates were resistant to one or more antimicrobials. Resistance to only tetracycline predominated among the cattle isolates (n = 89; 65.9%) with most resistant strains belonging to ST-459 (96.5%) or ST-982 (86.4%). Among the 22 STs identified, STs 459 and 982 were more prevalent in one feedlot, which reported the use of chlortetracycline in feed upon arrival of a new herd. PCR-based fingerprinting demonstrated that the ST-982 isolates from cattle and humans had identical banding patterns, suggesting the possibility of interspecies transmission. Resistance to macrolides (1.5%) and ciprofloxacin (16.3%) was also observed; 14 of the 22 ciprofloxacin resistant isolates represented ST-1244. Together, these findings demonstrate a high prevalence of antimicrobial resistant C. jejuni in cattle and identify associations with specific genotypes. Continuous monitoring and identification of risk factors for resistance emergence are imperative to develop novel methods aimed at decreasing pathogen persistence in food animal reservoirs and the frequency of resistant infections in humans.